Regional Migration in Turkey: Its Directions and Determinants - Ayse Nilay Evcil; Gulay Basarir Kiroplu; Vedia Dokmeci (European Regional Science Association (ERSA), 2006)
46th European Congress of the Regional Science Association August 30th -September 3rd 2006 Volos-Greece Regional Migration in Turkey: Its Directions and Determinants A.Nilay Evcil, Vedia Dökmeci, Gülay Baþarýr Kýroðlu Istanbul-Turkey Abstract It is clear that urbanization is a natural outgrowth of industrialization. But, in developing countries industrialization lag behind the rate of urbanization which involves much more rapid migration. In the case of Turkey, urbanization is mostly related with huge population growth in cities. So, it is worth to understand migration flows to benefit from population's spatial distribution. Thus, this paper aims to show the attributes of regional migration in Turkey. First, geographic regions are compared with each other according to different migration directions with the help of multivariate analysis of variance (MANOVA). The results show that, when four different migration directions are considered (from urban-to- urban, urban-to-rural, rural-to-urban and rural-to-rural) the seven regions possess different attributes such as geographic conditions, its working population distribution, job opportunities etc. It is also worth that as a common characteristic (except the Black Sea Region): migration direction mostly takes place from urban-to-urban (even in least urbanized regions) which points to a more advanced stage of urbanization. It must also be paid attention to the migration direction occurring from urban-to-rural areas in all regions (except the Black Sea Region) which has been stimulated by the economic crisis in 2001 and the investment in the rural areas. Second, multiple regression analysis is performed in order to determine the factors most related to net migration rate. In the near future, the Marmara and Aegean regions will still receive more migrants if other regions have poor socioeconomic conditions and inadequate job opportunities. Added to this, informal economy will continue to augment, since most of migrants are unskilled for manufacturing or service sectors. As a result, the government may not be able to collect taxes. So, migration on one hand bring vitality to an area, but, on the other hand , it creates some socio-economic problems. This paper also aims to compare migration directions between 1990 and 2000. It is found that migration direction still takes place from urban to urban.
Keywords: 330; Regional migration; Turkey; regional differences; statistical analyses